RICE SUPPLY CHAINS IN INDONESIA: HOW DO THEY WORK? - Joni Murti Mulyo Aji (UPT Penerbitan Universitas Jember, 2012)
The objective of this research is to identify how rice supply chains in Indonesia work. The nature of product, financial and information flows of rice supply chains inIndonesia are identified; and the relationships in the rice supply chains are explored. This research is guided by a social constructionist paradigm, thus it is primarily qualitative in nature. The research applies case study approach and inductive analysis. Findings across all cases indicate that contemporary rice supply chains are characterised by transactional and asymmetric dependence-based relationships. Although possible, collaborative supply chain management is difficult to implement especially in the absence of the government role to facilitate the development of more collaborative supply chains.